Non-governmental organizations’ influence on tackling black carbon in the shipping industry - Jialin, Han (Polar Research Institute of China - PRIC, 2016)
This paper reviews the achievements of some typical non-governmental organizations (NGOs) in reducing black carbon emissions from shipping which enjoy the consultative status offered by the International Maritime Organization. It discusses the roles of the specific NGOs in dealing with black carbon in the Arctic region from the perspective of global governance to gain insights to guide our involvements in the Arctic affairs and shipping in the region by taking the advantages of NGOs’ influence on the proceedings of international negotiations, our national policy development, the improvement of industrial practices and public perceptions.